2015
DOI: 10.1159/000369676
|View full text |Cite
|
Sign up to set email alerts
|

MiR-146b-5p Promotes Metastasis and Induces Epithelial-Mesenchymal Transition in Thyroid Cancer by Targeting ZNRF3

Abstract: Background/Aims: Micro-RNA (miR)-146b-5p is overexpressed in papillary thyroid carcinoma (PTC) and associated with extrathyroidal invasion and advanced tumor stage. In the present study, we showed that miR-146b-5p is upregulated in PTC with lymph node metastasis. Methods: A computational search and luciferase assay identified zinc RING finger 3 (ZNRF3), a negative regulator of Wnt/β-catenin signaling, as a direct target of miR-146b-5p in PTC. Results: MiR-146b-5p promoted migration and invasiveness and induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
108
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 25 publications
11
108
0
1
Order By: Relevance
“…However, it is not clear how TSHR suppresses EMT. Previous studies have demonstrated that microRNA (miRNA/miR) serves an important role in EMT; for example, miR-146b-5p induces EMT through the regulation of Wnt/β-catenin signaling (19,20) and the miR-200 family inhibits polycomb complex protein BMI1, and zinc finger E-box-binding homeobox 1 and 2, to suppress EMT (21)(22)(23). Further studies are required to demonstrate whether TSHR regulates EMT through miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear how TSHR suppresses EMT. Previous studies have demonstrated that microRNA (miRNA/miR) serves an important role in EMT; for example, miR-146b-5p induces EMT through the regulation of Wnt/β-catenin signaling (19,20) and the miR-200 family inhibits polycomb complex protein BMI1, and zinc finger E-box-binding homeobox 1 and 2, to suppress EMT (21)(22)(23). Further studies are required to demonstrate whether TSHR regulates EMT through miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…64 MicroRNAs are increasingly recognized as important regulators of EMT and of CSCs. [65][66][67][68][69][70] Recent studies have shown that the miR-200 family has a major regulatory role in EMT. 65 The miR-200 family has been shown to regulate EMT induced by EGF/EGFR 66 and also by targeting TGFβR1.…”
Section: Non-coding Rnas and Emt Micrornas And Emtmentioning
confidence: 99%
“…MiRNAs also have regulatory roles in well-differentiated thyroid cancers during EMT. [68][69][70] MiR-146b-5p has been shown to regulate PTC cells during EMT. 69 Hardin et al 36 used a TGFβ-induced model of EMT to show that miR-146b-5p was initially upregulated during the first fourteen days of TGFβ treatment, which was followed by downregulation of this microRNA with subsequent treatment for two weeks.…”
Section: Non-coding Rnas and Emt Micrornas And Emtmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of PTC patients is associated with their age, tumor size, lymph node invasion and distant metastasis (7). Currently, the standard therapeutic treatment for PTC is complete thyroidectomy followed by radioiodine and levothyroxine therapy (8).…”
Section: Introductionmentioning
confidence: 99%